(untitled) (The Pakistan Development Review, 2001)
Pak-rupee exchange rates vis-à-vis many currencies of the industrial world have weakened continuously and persistently since Pakistan abandoned fixed exchange rates in April 1982. This proposition is strongly supported by descriptive test statistics, as shown in Table 1, such as mean, standard deviation and coefficient of variation of six Pak rupee exchange rates—against the U.S. dollar, British pound, German mark, Japanese yen, Swiss franc and French franc—over the period 1982q1-2000q4. Based on these descriptive statistics, it is evident that Pak rupee has depreciated persistently against all currencies of the industrial countries in question over the period under investigation; for example, it has depreciated by 324.05 percent against the British pound, 406.360 percent against the U.S. dollar, 344.53 percent against the French franc, 498.48 percent against the Swiss franc, 477.78 percent against the German mark and 986.25 percent against the Japanese yen since April 1982. As evidenced by coefficient of variation, Pak rupee has weakened enormously against all currencies of the industrial world, while it has weakened relatively more alarmingly against the Japanese yen, Swiss franc and German mark.